2012
DOI: 10.1177/1420326x12461801
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of modern transitions on thermal comfort in vernacular dwellings in warm-humid climate of Sugganahalli (India)

Abstract: Sugganahalli, a rural vernacular community in a warm-humid region in South India, is under transition towards adopting modern construction practices. Vernacular local building elements like rubble walls and mud roofs are given way to burnt brick walls and reinforced cement concrete (RCC)/tin roofs. Over 60% of Indian population is rural, and implications of such transitions on thermal comfort and energy in buildings are crucial to understand. Vernacular architecture evolves adopting local resources in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In addition to the building orientation, research shows that natural ventilation improves thermal comfort in buildings that are located in hot and humid climates [45][46][47][48][49][50]. Natural ventilation can be become an integral part of the building envelope by introducing any one of the following ventilation elements viz., wind scoop, wind tower, chimney, double façade, atrium, ventilation chamber, embedded duct and/or ventilation opening in the facade [51,52].…”
Section: Factors Influencing Thermal Comfort Of Buildingmentioning
confidence: 99%
“…In addition to the building orientation, research shows that natural ventilation improves thermal comfort in buildings that are located in hot and humid climates [45][46][47][48][49][50]. Natural ventilation can be become an integral part of the building envelope by introducing any one of the following ventilation elements viz., wind scoop, wind tower, chimney, double façade, atrium, ventilation chamber, embedded duct and/or ventilation opening in the facade [51,52].…”
Section: Factors Influencing Thermal Comfort Of Buildingmentioning
confidence: 99%
“…Other studies on vernacular heritage focused on field measurements in order to quantify the thermal performance of vernacular architecture. 4749 Saïd et al. 48 described the monitoring approach and commented on the results of the long-term investigation of the hydrothermal performance of the building envelope of a heritage house located in Ottawa.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Dili et al 20 studied vernacular and conventional dwellings in Kerala, India, with warm-humid climate, and confirmed that vernacular dwellings outperformed conventional dwellings in maintaining indoor comfort across seasons. Shastry et al 21 studied the impact of modern transitions on rural dwellings in West Bengal, India, and found an increase in average indoor temperatures from 7 to 10 °C. Given the lower EE and OE energy and higher resilience to maintain indoor thermal comfort in response to wider variations in weather conditions, vernacular dwellings could hold important insights for mitigation and adaptation to climate change.…”
Section: Literature Reviewmentioning
confidence: 99%
“… The current study is limited to understanding the thermal performance of the dwellings to changing climate. Studies have reported increased discomfort among occupants due to transitions 20 , 21 as well as climate change 2 . The response of the occupants to changing climate and performance of dwellings should shed light on possible adaptation strategies since rural population tend to be proactive in responding to change.…”
Section: Limitations Of the Study And Scope For Future Workmentioning
confidence: 99%